Metode Penetapan Kadar Meloxicam Dalam Darah Manusia In Vitro Secara Kromatografi Cair Kinerja Tinggi - Harmita, Harmita; Mansur, Umar; Firnando, Firnando (UI Scholars Hub, 2004)
Until nowadays study of drug profile inside body (pharmacokinetic) and its development is still an interesting topic under pharmaceutical service. Development of an accurate analysis method for small quantity of drug in blood is an important step, HPLC method usually recommended for this purpose. Observation in studying the optimal method to analyze drug in human blood by using internal standard has been done for meloxicam, a new generation of NSAID. Two things has been focused to this observation, finding an ideal internal standard for meloxicam and testing the recovery of meloxicam in blood sample by in vitro. Coefficient of distribution of many samples (piroxicam, trimetropim, caffeine, salisilamid) gives caffeine as recommended internal standard for meloxicam. The recovery test gives 83,58% ± 3,802%, 74,37% ± 0,711%, 82,14% ± 1,937% for analysis meloxicam in human blood without internal standard; and 41,58% ± 1,108%, 61,60% ± 1,049%, 56,88% ± 0,478% for analysis meloxicam in human blood within internal standard.